Conservation importance of the melliferous plants of the Bulgarian flora (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
The paper presents a classification of 1010 species, belonging to 296 genera and 84 families of wild melliferous plants. A particular attention is given to the characteristics of the conservational importance of these plants at national and international level. Two hundred and one of these species belonging to 71 genera and 36 families were considered to have some conservational status in Bulgaria and Europe. Many of them are endemics for Bulgaria and/or Balkan Peninsula and are protected by the national Bulgarian legislation or by international conventions ratified by Bulgaria. The results indicate that substantial part of melliferous plant species of the Bulgarian flora is of high conservation value.
Keywords: Bulgaria, flora, melliferous plants, conservation value.